Study on protein enrichment of rice bran using local yeast for wild pig performance - INTHAXAY, Sysavai; CHANTHAKHOUN, Vongpasith; VILAYSACK, Visam; KANDEE, Thanousinh; MANIVANH , Nouphone; MITTHAVONG, Somhuk (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The aim of the study was to evaluate the effect of rice bran fermented with yeast on growth performance of wild pig, the objectives were compared on total feed intake, Daily gain, DM feed conversion, and economic income of wild pig. There were 4 treatments and design in RCBD with 3 replications of each treatment. Growing wild pig (n=12 heads), this experiment was conducted at Department of Animal Science Farms, of Faculty of Agriculture and Forest Resource, Souphanouvong University, this experiment was used 120 days and was started from 6-12/2020. The treatments were: T1= Rice bran 100% T2= Rice bran 50% and Corn 50% T3= Rice bran 50% and Complete feed 50% T4= Rice bran fermented with yeast 50% and Corn 50% The result showed that: DM was highest with rice bran, lower with corn and complete feed as pig feed, but for the crud protein was high with complete feed and lowest with rice bran. Total feed intake, g/day and DM feed intake, g/kg LW, there were different (Pro<0.001) and highest on treatment 3 (T3) by supplemented with pig complete feed and lowest on treatments 4. DM feed conversion ratio was improved by supplemented with pig complete feed or better with complete feed and battest fed. Initial Live Weight there was no different (Pro=1.00), but final weight there was different (Pro<0.001), and better by supplemented with comeplete feed and lower with corn and rice bran fermented with yeast as treatments T4 and T2 and lowest fed only rice bran. Live weight change there was different (Pro<0.05) and highest on treatment 3 of 39.56 g/head, lower of the treatments 4; 2 and 1 at the level 12.03; 11.96 and 8.86 kg/head. Average Daily Gain (ADG) there were different (pro<0.05) and highest on treatment 3 of 329.72 g/day, lower of the treatments 4; 2 and 1 at the level 100.27; 99.72 and 73.88 g/day. Economic income was better with T3 and lower T2 and T4 and lowest on treatment T1.